73. Insight and Cerebello-Cortical Connectivity in Adolescents at Ultra High-Risk of Schizophrenia. (20th March 2017) - Clark, Sarah; Ahmadi, Aral; Bernard, Jessica; Turner, Jessica; Mittal, Vijay
Abstract: Background: According to the cognitive dysmetria theory, symptom and behavioral features of psychosis are influenced dysfunctional connections between the cerebellum and cortex. Insight into illness may be one such thought process, and in schizophrenia, is associated with brain function of large-scale networks involved in self-reflection and cognitive control. However, while there is also limited evidence that insight is impaired in the prodromal phase of psychosis, there have been no studies examining underlying brain connectivity. We investigated whether insight is associated with cerebellocortical connectivity of major brain networks in adolescents at ultra high risk (UHR) of schizophrenia, as this may be an early indicator of psychosis risk. Methods: Data from a larger UHR study was used, including 37 UHR adolescents and 33 controls assessed with the Structured Interview of Prodromal Symptoms, Scale to Assess Unawareness of Mental Disorder, and Beck Cognitive Insight Scale. Dimensions of insight included clinical insight (awareness of having a mental disorder); and cognitive insight (self-reflectiveness and self-certainty). Participants also underwent resting state functional MRI scans. Functional connectivity was calculated between right and left crus I of the cerebellum and nodes of the default mode network (DMN; PCC/precuneus), central executive network (CEN; dorsolateral prefrontal cortex(dlPFC)), and cingulo-opercular network (CON; anterior insula/frontal operculum (aI/fO)). Hierarchical regression was calculated with functional connectivity as the dependent variable, covarying for head motion, including group and insight dimension as predictors, and a group insight dimension interaction. Results: There was a significant group by self-certainty interaction for connectivity between the left crus I and right dlPFC ( R 2 = .089). There was also a significant group by self-certainty interaction for connectivity between the left crus I and right aI/fO ( R 2 = .138). Both significant interactions demonstrated a negative relationship between self-certainty and connectivity in the UHR group but no significant relationship in the control group. Conclusion: Cerebello-prefrontal connectivity appears to be associated specifically with self-certainty in this UHR sample. High self-certainty, which is related to thought disorder in schizophrenia, was associated with weaker connectivity between the posterior cerebellum and prefrontal cortex. Results support the cognitive dysmetria theory, as weaker cerebello-prefrontal connectivity was associated with less flexible thinking about one's own cognitions.